Monoclonal B lymphocytosis versus chronic lymphocytic leukemia: Factors affecting implementation of an absolute threshold1. Issue 3 (8th March 2013) - Rollins‐Raval, Marian A.; Fisher, Jason; Craig, Fiona E.
Abstract: Background: Laboratories utilize diverse methods to determine the absolute count used to distinguish chronic lymphocytic leukemia (CLL) from monoclonal B lymphocytosis, with many using dual platform (DP) methods (flow cytometric percent of CLL‐like B cells × hematology analyzer white blood cell count). However, flow cytometric tube‐to‐tube variation may make interpretation difficult, particularly when the CLL‐like B‐cell count straddles the recommended threshold. This study investigates the extent, and potential sources, of this variability. Methods: Flow cytometric enumeration was performed on 20 samples with CLL‐like B cells and 10 control specimens using single platform (SP) and two DP tubes A: kappa, lambda, CD5, CD10, CD19, CD38, CD45, CD20 and B: FMC‐7, CD23, CD19, CD5, with and without racking to remove doublets. In addition, reproducibility studies were performed. Results: Three specimens showed discordant CLL‐like B‐cell counts relative to the threshold of 5 × 10 9 /L. Bland–Altman analysis demonstrated a systematic bias with DP Tube B > A (5.9%) and SP > DP Tube A (9.5%). The doublet percent varied between specimens, but did not account for the bias between DP tubes. Variation was also seen in enumeration of other cell types, suggesting multiple potential sources of inconsistency. Conclusions: Significant tube‐to‐tube variation may be seen in CLL‐like B‐cell counts. The precise cause of these differences is uncertain, but is likely multifactorial. If the clinical utility of an absolute threshold for the diagnosis of CLL can be confirmed, it will be important to establish recommendations for standardization, similar to those employed for CD4 and CD34 enumeration. © 2013 International Clinical Cytometry Society